O edukacji włączającej – z uwzględnieniem problemu bezpieczeństwa uczniów w kontekście formalnoprawnym - Jadach, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2021)
The key issue of this article is inclusive education in connection with the formal and legal aspects of students’ safety when they are staying in educational institutions. In the first part, author describes the basic assumptions of the social model of education and it’s international conditions, also referring to solutions that have been recently implemented in the Polish education system. The second part indicates the problems that may be met by educational institutions and teachers trying to achieve a state of full inclusion. They relate to the school’s caring function in terms of security guarantees. The diversity of student population, especially wide range of educational needs may make it impossible for teachers to develop specific approach to individual pupil. It’s caused by formal items, largely determined by the financial situation of particular local government units.